Proposed Marketing Strategy To Increase Brand Awareness: Case Study dRyshirt - Reswanti Julian Pratama, Roro Arinda; B. Paramarta, Riawan (The Indonesian Journal of Business Administration, 2016)
Abstract. Purpose – Purpose of research is to help dRyshirt business in increasing its product sales and increase brand awareness "dRyshirt" on the minds of the public, especially for around town Bandung. Methodology/approach – In this research, using qualitative methods which aim to take a direct data survey, interviews and questionnaires. amount of sampling used in this research was 400 respondents in Bandung. Findings – Results of this research, there are two problems that occur on dRyshirt. First, lack of brand awareness with consumers and second declining number of buyers caused by promotional activities carried dRyshirt less attractive. It concluded that dRyshirt need to improve the way of promotion and good communication to consumers. Research Limitation – In this research has been established limitations in conducting research. This research is only done for the area of Bandung city, then only focus on brand awareness dRyshirt, and this research is targeted for men aged 20 years and over who like to shop online. Keywords: Brand Awareness, Communication Strategy, Fashion Industry, Marketing Strategy.